2022
DOI: 10.3390/jcm11133886
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Predictors of Fatigue in Post-COVID Syndrome

Abstract: Fatigue is one of the most disabling symptoms in several neurological disorders and has an important cognitive component. However, the relationship between self-reported cognitive fatigue and objective cognitive assessment results remains elusive. Patients with post-COVID syndrome often report fatigue and cognitive issues several months after the acute infection. We aimed to develop predictive models of fatigue using neuropsychological assessments to evaluate the relationship between cognitive fatigue and obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…However, the questionnaire responses revealed a wide variety of symptoms potentially interfering with work capacity, and a careful, individualized assessment of each symptom would be needed in these patients. Regarding cognitive function, the Stroop test was the most associated test, which is in accordance with previous studies in which the Stroop test is one of the most impaired tests in PCS and more associated with fatigue [ 12 , 22 , 23 , 24 ]. The results remained significant even after excluding those patients requiring ICU admission or ventilatory assistance.…”
Section: Discussionsupporting
confidence: 91%
“…However, the questionnaire responses revealed a wide variety of symptoms potentially interfering with work capacity, and a careful, individualized assessment of each symptom would be needed in these patients. Regarding cognitive function, the Stroop test was the most associated test, which is in accordance with previous studies in which the Stroop test is one of the most impaired tests in PCS and more associated with fatigue [ 12 , 22 , 23 , 24 ]. The results remained significant even after excluding those patients requiring ICU admission or ventilatory assistance.…”
Section: Discussionsupporting
confidence: 91%
“…Fatigue usually has a physical and a cognitive dimension, which may have different pathophysiological mechanisms. 5 , 6 The detection of brain damage in neuroimaging studies in patients with post-COVID syndrome and in histopathological studies in individuals who died due to COVID-19 supports the hypothesis of central nervous system dysfunction in patients with this condition. 7-10 Furthermore, research with transcranial magnetic stimulation has found connectivity changes potentially associated with gamma-aminobutyric acid (GABA)-ergic neurotransmission dysfunction.…”
Section: Introductionmentioning
confidence: 75%
“…Although some studies suggest that dorsolateral prefrontal tDCS could enhance cognitive performance, especially attention function and working memory, recent meta-analyses have shown conflicting results. 42 , 43 In a recent study into post-COVID syndrome, we found that the Stroop test was the test that most strongly correlated with subjective fatigue, 6 although this test is also associated with other cognitive functions. Thus, our results suggest that short-term prefrontal tDCS has no significant effects on cognitive fatigue as measured by subjective and objective tests.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Physical fatigue can be measured using a variety of physiological measures, such as those obtained from heart rate, nerve conduction studies, and electrophysiological examinations 13 . Cognitive fatigue, also called brain fog, 5 is typically measured by self-report or by a decline in performance of a cognitively demanding task 22 …”
Section: Introductionmentioning
confidence: 99%